Is 'Being There' Enough? Explorations of Incarnational Missiology with Chaplains. Issue 2 (3rd April 2017) - Dunlop, Sarah
Abstract : Based on the findings of case study research, this paper describes how chaplains conceptualize their ministry in the public sphere, as 'being there'. They report that they see their work as incarnating something of God and being similar to the parish priest who cares for everyone within a community. They see their role in terms of connecting people to God and, at times, to the church. The chaplains' sense of 'being there' as a missiology is analyzed through a discussion of the theological conceptions of incarnation and imago Dei . The paper concludes that the presence of chaplains within public spheres embodies a much-needed paradigm of mission. Drawing on the concept of prophetic dialogue, this paper argues that yes and no — 'being there' is enough in terms of the ministry of chaplains, but the theology of 'being there' needs to be not only in dialogue with the context, but also be prophetic.